Social work research and the analysis of social data - Philip, Alistair E.; McCulloch, J. Wallace (James Wallace), 1921-; Smith, N. J. (Norman James) (Pergamon international library of science, technology, engineering, and social studies., 1975)
Social Work Research and the Analysis of Social Data is a research book that describes both methodology and data analysis in logical sequence as a basis in order to begin the application of scientific method to psycho-social problems.